A micro strain sensor and a preparation method and application thereof

CN117704953BActive Publication Date: 2026-10-09NANKAI UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311732731.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-16
Publication Date
2026-10-09
Estimated Expiration
2043-12-16

AI Technical Summary

Technical Problem

该柔性压力传感器阵列可以在三维表面进行压力检测,但是分辨率为1-10mm,对于人体脉搏跳动等微小形变难以进行三维成像

Benefits of technology

[0022] 1) This invention utilizes the Ag-S coordination bonds formed between silver nanowires and thiol-modified titanium carbide nanosheets (S-MXene) to obtain a conductive film with a layered structure, which is then transferred and embedded in an elastomer. The conductive film is etched, and the conductive material is formed into leads and electrodes by printing or vapor deposition techniques. This preparation method is simple, the materials are readily available, and it is conducive to large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117704953B_ABST
    Figure CN117704953B_ABST
Patent Text Reader

Abstract

The application relates to a micro strain sensor and a preparation method and application thereof, and the method comprises the following steps: configuring titanium carbide nanosheets into dispersion liquid A by taking DMF as a solvent, and configuring silver nanowires into dispersion liquid B by taking ethanol as a solvent; adopting a layer-by-layer self-assembly technology, dispersion liquid A and dispersion liquid B are sequentially coated on a glass substrate to obtain a conductive film; an elastomer solution or an elastomer precursor liquid is coated on the surface of the conductive film to form a flexible substrate; a micro strain sensing unit is etched through a laser etching technology; and electrodes and connecting lines are introduced in the micro strain sensing unit through a printing or evaporation technology. Through the formation of a high-energy and dynamic reversible sulfur-silver coordination bond between the surface mercapto of S-MXene and the surface silver atoms of silver nanowires, the stress distribution and crack growth behavior in the brittle conductive film are regulated, so that a high-density micro-nano crack network is formed in the conductive film. The sensing area of the obtained strain sensor can be as low as 0.25mm 2 In the range of 0.0005-40% strain, a huge change of resistance value can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sensing materials and device design, specifically to a miniature strain sensor, its fabrication method, and its applications. Particularly, it relates to a sensor and high-density sensing array based on a microcrack mechanism, characterized by a large operating range, long lifespan, ultra-low detection limit, and high sensitivity. It is primarily used for human motion information imaging and medical 3D imaging, and has enormous application prospects in human-computer interaction, electronic skin, bionic robots, and 3D imaging. Background Technology

[0002] With the widespread adoption of flexible electronic devices, flexible wearable sensors and arrays have attracted considerable attention. In the field of pulse diagnosis in Traditional Chinese Medicine, high-sensitivity, high-precision sensor arrays can achieve three-dimensional imaging of the instantaneous pulse beat. However, during the stretching process, large cracks in the conductive nanomaterials of the sensor unit not only lead to a larger device size and reduced array density but also a smaller operating range, making it unable to adapt to large strains. Introducing elastic polymers, wrinkled structures, or biomimetic structures into the sensor can improve the operating range, but the sensitivity decreases dramatically. Therefore, developing sensors and high-density arrays with ultra-low detection limits, high sensitivity, and a large operating range is of great significance.

[0003] Chinese patent publication CN213242596U discloses a sensor array with a resolution of 60 μm, but its structure is complex and its fabrication process is cumbersome. Chinese patent publication CN113739961A discloses a flexible pressure sensor array and its manufacturing method. This flexible pressure sensor array can detect pressure on three-dimensional surfaces, but its resolution is only 1-10 mm, making it difficult to perform three-dimensional imaging of minute deformations such as human pulse beats. Non-patent literature (Composites Science and Technology, 2020, 200:108437) describes a flexible high-performance strain sensor that electrostatically self-assembles carbon nanoparticles onto polyurethane foam. This strain sensor has a working range of 60% and a sensitivity as high as 43,000. Based on the high sensitivity of this strain sensor, a 5×5 mm sensor array with a resolution of 10×10 mm was fabricated, which can be used to identify the pressure and position of objects. However, this sensor has not been further studied in terms of ultra-low detection limits, and the large resolution of the sensor array makes it difficult to perform three-dimensional imaging of minute deformations.

[0004] Therefore, developing a sensor and high-density array with a large operating range, high sensitivity, long service life, and ultra-low detection limit remains challenging and is an important research topic. Summary of the Invention

[0005] Currently, most sensor units suffer from large-scale cracks in conductive nanomaterials during stretching, resulting in large device sizes, reduced array density, and limited operating ranges, making them unsuitable for large strains. Therefore, this invention provides a miniature strain sensor, its fabrication method, and its applications.

[0006] To achieve the above objectives, the present invention provides a method for fabricating a miniature strain sensor, comprising the following steps:

[0007] S1. Thiol-modified titanium carbide nanosheets were prepared as dispersion A using N,N-dimethylformamide as solvent, and silver nanowires were prepared as dispersion B using ethanol as solvent. Using layer-by-layer self-assembly technology, dispersion A and dispersion B were sequentially and repeatedly coated on a glass substrate, and the solvent was evaporated to obtain a brittle conductive film with a layered structure.

[0008] S2. Coat the surface of the conductive film with an elastomer solution or elastomer precursor liquid, heat to evaporate the solvent or cure to form a flexible substrate on the surface of the conductive film, and peel the conductive film with the flexible substrate off the glass substrate to obtain the sensor body.

[0009] S3. Using laser etching technology, areas of 0.25-100 mm² are etched onto the sensor body. 2 The region is used as a micro strain sensing unit;

[0010] S4. Electrodes and connecting lines are introduced into the micro strain sensing unit through printing or vapor deposition technology to obtain a micro strain sensor.

[0011] As a further preferred embodiment of the present invention, the thiol-modified titanium carbide nanosheets are prepared by the following steps:

[0012] γ-Mercaptopropyltriethoxysilane coupling agent was added dropwise to a mixed solution of deionized water and ethanol for hydrolysis. The hydrolyzed solution was then added dropwise to an aqueous solution of MXene (Ti3C2Tx), and the reaction was carried out under heating with stirring. The resulting suspension was centrifuged and washed to obtain thiol-modified titanium carbide nanosheets. Preferably, deionized water and ethanol were mixed at a volume ratio of 5:1.

[0013] As a further preferred technical solution of the present invention, the layer-by-layer self-assembly technology is one of layer-by-layer immersion technology, layer-by-layer spraying technology, and layer-by-layer spin coating technology.

[0014] As a further preferred embodiment of the present invention, the conductive film has a multilayer structure with a total thickness of 0.5-3 micrometers.

[0015] As a further preferred embodiment of the present invention, the flexible substrate is a styrene-based block copolymer thermoplastic elastomer or a silicone elastomer polydimethylsiloxane, or one of polyethylene terephthalate, poly4-methylpentene, polyvinyl alcohol, polyamide thermoplastic elastomer, ethylene-vinyl acetate copolymer, polyacrylate, polymethacrylate, polyethylene oxide, or polyolefin thermoplastic elastomer; the styrene-based block copolymer thermoplastic elastomer is SBS, SEBS, or SIS. The flexible substrate is an elastomer material used to embed conductive films, which is a standard procedure in flexible sensor fabrication technology.

[0016] As a further preferred technical solution of the present invention, the area etched to form the micro strain sensing unit in step S3 is rectangular, with a length of 100-5000μm and a width of 100-5000μm.

[0017] As a further preferred technical solution of the present invention, in step S3, multiple micro strain sensing units are etched on the sensor body and distributed in an array; in step S4, electrodes and connecting lines are introduced into the micro strain sensing units by printing or vapor deposition technology, and the array-distributed micro strain sensing units are constructed into a high-density strain sensing array.

[0018] As a further preferred technical solution of the present invention, the density of the micro-strain sensing units in the high-density strain sensing array is 1-100 per square centimeter.

[0019] According to another aspect of the present invention, a miniature strain sensor is also provided, which is prepared by the method described above.

[0020] According to another aspect of the present invention, the present invention also provides an application of a micro strain sensor, which can be used for flexible three-dimensional pulse acquisition and signal processing, material sensing and recognition, or human-computer interaction interface.

[0021] Compared with the prior art, the present invention has the following beneficial technical effects:

[0022] 1) This invention utilizes the Ag-S coordination bonds formed between silver nanowires and thiol-modified titanium carbide nanosheets (S-MXene) to obtain a conductive film with a layered structure, which is then transferred and embedded in an elastomer. The conductive film is etched, and the conductive material is formed into leads and electrodes by printing or vapor deposition techniques. This preparation method is simple, the materials are readily available, and it is conducive to large-scale industrial production.

[0023] 2) This invention utilizes the formation of highly energetic and dynamically reversible sulfur-silver (S-Ag) coordination bonds between the thiol groups on the surface of S-MXene and the silver atoms on the surface of silver nanowires to regulate the stress distribution and crack growth behavior in brittle conductive films, thereby forming a high-density micro-nano crack network in the conductive film. This solves the problem of the inability to miniaturize crack strain sensors. The high-density micro-cracks can significantly reduce the lower limit of the strain range, thereby increasing the upper limit of the strain range.

[0024] 3) This invention solves the problem of the inability to miniaturize crack strain sensors, and the resulting micro-strain sensor can have a sensing area as low as 0.25 mm². 2 The sensor can achieve a large change in resistance within a strain range of 0.0005-40%, exhibiting excellent sensing sensitivity, fast response time, and superior sensing stability. The high-density strain sensor array can achieve a sensing unit density of up to 100 units per square centimeter, enabling applications such as flexible three-dimensional pulse acquisition and signal processing analysis—a feat currently unattainable by most sensors. Attached Figure Description

[0025] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments.

[0026] Figure 1-1 This is a schematic diagram of the structure of the miniature strain sensor according to Embodiment 1 of the present invention;

[0027] Figure 1-2 The X-ray photoelectron spectrum of the miniature strain sensor of Embodiment 1 of the present invention is shown below.

[0028] Figure 2 This is a scanning electron microscope image of the cross-section of the miniature strain sensor of Embodiment 1 of the present invention;

[0029] Figure 3 The working curve of the miniature strain sensor in Embodiment 2 of the present invention;

[0030] Figure 4 This refers to the lifespan of the miniature strain sensor in Embodiment 2 of the present invention;

[0031] Figure 5 The detection limit of the miniature strain sensor in Embodiment 2 of the present invention;

[0032] Figure 6 This is a scanning electron microscope image of a nanocrack in the micro-strain sensor of Embodiment 3 of the present invention;

[0033] Figure 7 This is a schematic diagram of the sensing array in the miniature strain sensor of Embodiment 3 of the present invention;

[0034] Figure 8This is a scanning electron microscope image of the sensing array in the miniature strain sensor of Embodiment 4 of the present invention;

[0035] Figure 9 This is a three-dimensional image of the human pulse from the miniature strain sensor of Embodiment 4 of the present invention.

[0036] Figure 1-1 In the middle: 1. S-MXene layer; 2. Silver nanowire layer.

[0037] The objectives, features, and advantages of this invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation

[0038] The specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustration and explanation only and are not intended to limit the present invention.

[0039] Unless otherwise defined, the technical terms used in the following embodiments have the same meanings as commonly understood by those skilled in the art to which this invention pertains. Unless otherwise specified, the experimental reagents used in the following embodiments are conventional biochemical reagents; and the experimental methods described are conventional methods.

[0040] Example 1:

[0041] The fabrication method of the miniature strain sensor provided in this embodiment is as follows:

[0042] (1) γ-mercaptopropyltriethoxysilane coupling agent (KH-580) was added dropwise to a mixed solution of deionized water and ethanol (volume ratio 5:1) for hydrolysis. After KH-580 was completely hydrolyzed, the hydrolyzed solution was added dropwise to MXene aqueous solution and heated and stirred at 60°C for 2 hours. The resulting suspension was centrifuged three times at 10,000 rpm using N,N-dimethylformamide (DMF) and then dispersed in DMF to obtain thiol-modified titanium carbide nanosheets (S-MXene), which were then prepared into an S-MXene / DMF dispersion with a concentration of 10 mg / mL.

[0043] (2) Weigh 100 μL of a 10 mg / mL S-MXene (Ti3C2Tx) / DMF dispersion and a 1 mg / mL silver nanowire / ethanol dispersion, respectively, and spin-coat them sequentially onto a glass slide at a rotation speed of 750 rpm for 12 s. Heat at 60 °C for 1 min, and repeat the process 7 times to obtain an S-MXene / silver nanowire conductive film on a glass substrate, with the structure shown below. Figure 1-1 As shown, the conductive film has a layered structure, with silver nanowire layer 1 and S-MXene layer 2 alternately stacked. Figure 1-2As shown, the silver-sulfur coordination leads to the shift of Ag 2d5 / 2 (368.4 eV) and Ag 2d3 / 2 (374.4 eV) in silver nanowires to 367.1 eV and 373.1 eV, respectively, proving the existence of sulfur-silver (S-Ag) coordination bonds.

[0044] (3) Weigh 2g of polyurethane 6210, 1g of (5-ethyl-1,3-dioxane-5-yl) methyl acrylate, and 0.3g of photoinitiator. Mix the three together and stir until homogeneous. Remove air bubbles by vacuuming and pour the mixture onto the surface of an S-MXene / silver nanowire conductive film. Cure under UV light for 5 minutes. Peel the film off the glass substrate to obtain the sensor body. Quench the sensor body and observe the cross-section; it can be seen to have a layered structure, such as... Figure 2 As shown.

[0045] (4) Use a laser marking machine to etch the sensor body obtained in step (3) into a miniature strain sensing unit (hereinafter referred to as sensing unit) with a module size of 1×1mm and a 6×6 array distribution.

[0046] (5) Weigh 5 mL of liquid metal (EGaIn) and use a direct writing printer to print electrodes and connecting lines on the 6×6 sensing unit obtained in step (4) to construct a high-density strain sensing array.

[0047] A resistance meter-mechanical-electric translation stage combined system was used to test the upper and lower limits of the working range, sensitivity, and response time of the micro-strain sensor, with spatial resolution consistent with the pixel (sensor unit) size. The obtained high-density strain sensor array has a strain detection range of 0.0005-100%, a sensing sensitivity (gauge factor) of 400, a sensing response time of 5 ms, a temporal resolution of 5 ms, and a spatial resolution of 1000 micrometers.

[0048] Example 2:

[0049] The fabrication method of the miniature strain sensor provided in this embodiment is as follows:

[0050] (1) γ-mercaptopropyltriethoxysilane coupling agent (KH-580) was added dropwise to a mixed solution of deionized water and ethanol (volume ratio 5:1) for hydrolysis. After KH-580 was completely hydrolyzed, the hydrolyzed solution was added dropwise to MXene aqueous solution and heated and stirred at 60°C for 2 hours. The resulting suspension was centrifuged three times at 10,000 rpm using N,N-dimethylformamide (DMF) and then dispersed in DMF to obtain thiol-modified titanium carbide nanosheets (S-MXene), which were then prepared into an S-MXene / DMF dispersion with a concentration of 8 mg / mL.

[0051] (2) Weigh 50 mL of S-MXene(Ti3C2Tx) / DMF dispersion with a concentration of 8 mg / mL and silver nanowire / ethanol dispersion with a concentration of 1 mg / mL respectively, and immerse the glass slide in them for 5 min. Heat at 45℃ for 2 min and repeat the operation 5 times to obtain S-MXene / silver nanowire conductive film on glass substrate.

[0052] (3) Weigh 10g of SEBS and dissolve it in 150mL of n-octane. Pour the solution onto the surface of the S-MXene / silver nanowire conductive film and heat it at 30°C for 1 hour. Peel the film off the glass substrate to obtain the sensor body.

[0053] (4) The sensor body obtained in step (3) is etched into sensing units arranged in an 8×8 array with a module size of 0.8×0.8mm using a laser marking machine. Its working range is tested using a resistance tester-mechanical-electric translation stage combined system, and the working curve is shown below. Figure 3 As shown, the maximum operating capacity is 130%; the service life is as follows. Figure 4 As shown, the sensor is cycled 10,000 times at 70% strain; the sensor's detection limit is as follows. Figure 5 As shown, the sensitivity is 498 and the detection limit is 0.05%.

[0054] (5) A gold thin film is deposited on the 8×8 sensing unit obtained in step (4) using vacuum evaporation technology as electrodes and connecting lines to obtain a high-density strain sensing array.

[0055] The strain detection range of the sensing unit of the obtained high-density strain sensing array is 0.01-100%, the sensing sensitivity (gauge factor) is 200,000, the sensing response time is 10ms, the time resolution is 50ms, and the spatial resolution is 800 micrometers.

[0056] Comparative Example 1:

[0057] This comparative example serves as the experimental control group for Example 2. Its preparation method is the same as in Example 2, except that: non-thiol-modified blank MXene is used to replace the thiol-modified titanium carbide nanosheets (S-MXene) of Example 2 to prepare an MXene / silver nanowire conductive film. Then, the same elastomer is used to embed the conductive film to obtain the sensor body. The sensor body is etched, with a maximum of 2×2 sensor units etched per unit area, resulting in a size of 4×4 mm. The strain detection range of the obtained sensor is 20%, the sensing sensitivity (gauge factor) is 100, the sensing response time is 1 s, and the time resolution is 1 s.

[0058] Example 3:

[0059] The fabrication method of the miniature strain sensor provided in this embodiment is as follows:

[0060] (1) γ-mercaptopropyltriethoxysilane coupling agent (KH-580) was added dropwise to a mixed solution of deionized water and ethanol (volume ratio 5:1) for hydrolysis. After KH-580 was completely hydrolyzed, the hydrolyzed solution was added dropwise to MXene aqueous solution and heated and stirred at 60°C for 2 hours. The resulting suspension was centrifuged three times at 10,000 rpm using N,N-dimethylformamide (DMF) and then dispersed in DMF to obtain thiol-modified titanium carbide nanosheets (S-MXene), which were then prepared into an S-MXene / DMF dispersion with a concentration of 8 mg / mL.

[0061] (2) Weigh 100 μL of S-MXene(Ti3C2Tx) / DMF dispersion with a concentration of 6 mg / mL and silver nanowire / ethanol dispersion with a concentration of 2 mg / mL respectively, spin-coat them on a glass slide at a rotation speed of 800 rpm for 10 s, heat at 60 °C for 1 min, and repeat the operation 10 times to obtain S-MXene / silver nanowire conductive film on glass substrate.

[0062] (3) Weigh 2g of polyurethane 6290, 1g of methyl acrylate (5-ethyl-1,3-dioxane-5-yl) and 0.3g of photoinitiator, mix the three together and stir evenly, remove air bubbles by vacuuming, pour onto the surface of S-MXene / silver nanowire conductive film, cure under ultraviolet light for 5 minutes, peel the film off the glass substrate to obtain the sensor body.

[0063] (4) Using a laser marking machine, the sensor body obtained in step (3) is etched into sensing units arranged in a 10×10 array with a module size of 0.5×0.5mm. The sensor is then stretched, and abundant microcracks can be formed on the sample surface, such as... Figure 6 As shown.

[0064] (5) Weigh 4 mL of carbon nanotubes (CNTs) and use a direct writing printer to print electrodes and connecting lines on the 10×10 sensing unit obtained in step (4) to obtain a high-density strain sensing array, such as... Figure 7 As shown.

[0065] The strain sensing unit of the obtained high-density strain sensing array has a strain detection range of 0.1-80%, a sensing sensitivity (gauge factor) of 10000, a sensing response time of 30ms, a temporal resolution of 100ms, and a spatial resolution of 500 micrometers.

[0066] Example 4:

[0067] The fabrication method of the miniature strain sensor provided in this embodiment is as follows:

[0068] (1) γ-mercaptopropyltriethoxysilane coupling agent (KH-580) was added dropwise to a mixed solution of deionized water and ethanol (volume ratio 5:1) for hydrolysis. After KH-580 was completely hydrolyzed, the hydrolyzed solution was added dropwise to MXene aqueous solution and heated and stirred at 60°C for 2 hours. The resulting suspension was centrifuged three times at 10,000 rpm using N,N-dimethylformamide (DMF) and then dispersed in DMF to obtain thiol-modified titanium carbide nanosheets (S-MXene), which were then prepared into an S-MXene / DMF dispersion with a concentration of 8 mg / mL.

[0069] (2) Weigh 1 mL of S-MXene(Ti3C2Tx) / DMF dispersion with a concentration of 5 mg / mL and silver nanowire / ethanol dispersion with a concentration of 1 mg / mL respectively, and spray them onto the glass slide with a spray gun. Heat at 50°C for 2 min and repeat the operation 10 times to obtain S-MXene / silver nanowire conductive film on glass substrate.

[0070] (3) Weigh 10g of PDMS part A and 1g of PDMS part B, mix them and stir evenly, remove air bubbles by vacuuming, and screen print them on the surface of the MXene / silver nanowire conductive film obtained in step (1) using a screen printing stencil. Heat at 80°C for 2 hours, peel the film off the glass substrate, and obtain the sensor body.

[0071] (4) Use a laser marking machine to etch the sensor body obtained in step (3) into a 12×12 array of sensor units with a module size of 0.7×0.7mm.

[0072] (5) Using vacuum evaporation technology, a platinum thin film is deposited on the 12×12 sensing unit obtained in step (4) as electrodes and connecting lines to obtain a high-density strain sensing array, the scanning electron microscope of which is as follows: Figure 8 As shown.

[0073] The strain detection range of the strain sensing unit of the obtained high-density strain sensing array is 0.0005-100%, the sensing sensitivity (gauge factor) is 200000, the sensing response time is 50ms, the time resolution is 70ms, and the spatial resolution is 1200 micrometers.

[0074] The miniature strain sensor in this embodiment can be applied to flexible three-dimensional pulse image acquisition and signal processing analysis, material sensing and recognition, human-computer interaction interfaces, etc. When applied to flexible three-dimensional pulse image acquisition and signal processing analysis, the obtained three-dimensional image of the human pulse is as follows: Figure 9 As shown.

[0075] While specific embodiments of the present invention have been described above, those skilled in the art should understand that these are merely illustrative examples, and various changes or modifications can be made to these embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is defined only by the appended claims.

Claims

1. A method for fabricating a miniature strain sensor, characterized in that, Includes the following steps: S1. Thiol-modified titanium carbide nanosheets were prepared as dispersion A using N,N-dimethylformamide as solvent, and silver nanowires were prepared as dispersion B using ethanol as solvent. Using layer-by-layer self-assembly technology, dispersion A and dispersion B were sequentially and repeatedly coated on a glass substrate, and the solvent was evaporated to obtain a brittle conductive film with a layered structure. S2. Coat the surface of the conductive film with an elastomer solution or elastomer precursor liquid, heat to evaporate the solvent or cure to form a flexible substrate on the surface of the conductive film, and peel the conductive film with the flexible substrate off the glass substrate to obtain the sensor body. S3. Using laser etching technology, areas of 0.25-100 mm² are etched onto the sensor body. 2 The region is used as a micro strain sensing unit; S4. Electrodes and connecting lines are introduced into the micro strain sensing unit through printing or vapor deposition technology to obtain a micro strain sensor.

2. The method for fabricating a micro-strain sensor according to claim 1, characterized in that, The thiol-modified titanium carbide nanosheets are prepared by the following steps: γ-mercaptopropyltriethoxysilane coupling agent was added dropwise to a mixed solution of deionized water and ethanol for hydrolysis. The hydrolyzed solution was then added dropwise to an aqueous solution of titanium carbide MXene, and the reaction was stirred under heating conditions. The resulting suspension was centrifuged and washed to obtain thiol-modified titanium carbide nanosheets.

3. The method for fabricating a micro-strain sensor according to claim 1, characterized in that, The layer-by-layer self-assembly technology is one of layer-by-layer immersion technology, layer-by-layer spraying technology, or layer-by-layer spin coating technology.

4. The method for fabricating a micro-strain sensor according to claim 1, characterized in that, The conductive film has a multilayer structure with a total thickness of 0.5-3 micrometers.

5. The method for fabricating a micro-strain sensor according to claim 1, characterized in that, The flexible substrate is a styrene-based block copolymer thermoplastic elastomer or a silicone elastomer polydimethylsiloxane, or one of polyethylene terephthalate, poly4-methylpentene, polyvinyl alcohol, polyamide, ethylene-vinyl acetate copolymer, polyacrylate, polymethacrylate, polyethylene oxide, or polyolefin thermoplastic elastomer; the styrene-based block copolymer thermoplastic elastomer is SBS, SEBS, or SIS.

6. The method for fabricating a micro strain sensor according to claim 1, characterized in that, In step S3, the area etched to form the micro strain sensing unit is rectangular, with a length of 100-5000 μm and a width of 100-5000 μm.

7. The method for fabricating a micro-strain sensor according to claim 1, characterized in that, In step S3, multiple micro-strain sensing units are etched on the sensor body and distributed in an array. In step S4, electrodes and connecting lines are introduced into the micro-strain sensing units through printing or vapor deposition technology to construct a high-density strain sensing array from the array-distributed micro-strain sensing units.

8. The method for fabricating a micro strain sensor according to claim 7, characterized in that, The density of micro-strain sensing units in the high-density strain sensing array is 1-100 per square centimeter.

9. A miniature strain sensor, characterized in that, It is prepared by the method described in any one of claims 1-8.

10. An application of the miniature strain sensor according to claim 9, characterized in that, Miniature strain sensors can be applied to flexible three-dimensional pulse acquisition and signal processing, material sensing and recognition, or human-computer interaction interfaces.

Citation Information

Patent Citations

  • Flexible pressure sensor array and manufacturing method thereof

    CN113739961A

  • Sensor array

    CN213242596U

  • Chitosan transparent conductive film based on silver nanowire network and preparation method thereof

    CN109524173A

  • Microcrack strain sensor and preparation method thereof

    CN114941980A